Analysis on the Mechanical Characteristics of Onshore Wind Power Generation Foundation Structure. Issue 1 (January 2021) - Zhou, Heng; Li, Xiaomin; Liu, Jing; Di, Shengjie
Abstract: Based on the 3D finite element method, considering the plastic damage model of concrete, the uncoordinated deformation relationship between steel foundation ring and concrete, and the coordinated displacement relationship between steel bars and concrete, this paper conducts a simulation analysis on onshore wind power generation foundation, and studies the stress characteristics of the foundation under ultimate load condition. The results show that the lower part of the steel foundation embedded plate is a weak part, which not only needs to pay attention to the tensile failure, but also needs to prevent the compression failure. Perforated steel bars arranged on the top of steel plates have a obvious stress effect, which obviously strengthens the connection between steel plates and concrete. With the weakening of the connection between steel foundation and concrete, the top displacement and relative displacement of the contact surface between steel plate and concrete gradually increase. With the increase of friction coefficient between steel foundation and concrete, the stress of perforated steel bars and the displacement of foundation ring top surface also decrease. The research results of this paper can provide an important reference for the design and reinforcement of infrastructure.